Process equipment information web-based system for process industries - Nur Izzati, Pakhor Anuar; Hanida, Abdul Aziz (AIP Publishing, 2023)
The Process Safety Management (PSM) standard consist of 14 elements to prevent and mitigate major accident including fire, explosion, and toxics release that may endanger a worker and the surrounding environment. The recent review of the PSM program by OSHA, Process Safety Information (PSI), and Mechanical Integrity (MI) elements were the most cited elements in organization audit. Process Equipment Information including material and energy balance, certificate, permits and approval, relief system design basis, ventilation of PSI is related to MI element; hence a complete compilation of process equipment information is vital for a robust PSI program that supports other PSM critical element including MI. However, lacking a systematic system to implement SI has hindered the effort to complete PSI compilation in a timely manner. This paper focuses on the development of a PSI web-based system focusing on process equipment coverage and compliance with PSM standards. The system was developed by an ionic framework for front-end technology and adapting Plan Do Check and Act (PDCA) concept as a backbone. The process equipment module could assist organizations to capture process equipment information including design code, equipment description, materials of construction, design basis, and electrical classification. The system has been tested via a case study using real plant data. From the case study the system can provide real-time process equipment data for employeesto refer, review, update, download, and communicate. In addition, the system features able the top management to doa self-check audit of equipment information completeness. A good agreement was also found from the focus group discussion.